A twilight for the complete nitrogen removal via synergistic partial-denitrification, anammox, and DNRA process - Hafiz Adeel Ahmad (Nature Portfolio, 2021)
Abstract The prolonged start-up time and low total nitrogen removal of anammox hinder its full-scale application. Herein, application of nano-zerovalent iron and low strength magnetic field in sole and in combination to abbreviate the start-up period and long-term process stability of anammox was carried out. The reactor’s anammox start-up with the only magnetic field (R3) was 34 days, saving 43.3% time compared with the control. The increase of nitrogen removal efficiency over the control was 43.7% during the start-up period. However, the reactor with the coupled treatment of nano-zerovalent iron and magnetic field (R4) was more stable with higher nitrogen removal efficiency (80%) at high nitrogen loading (5.28 kg/m3/d). Anammox gene copy number in R4 was highest after 180 days of culture, followed by nano-zerovalent iron (R2) and R3 reactor. The functional genes of denitrifying bacteria (nirK and nirS) were also identified in all reactors with higher copy numbers in R2, followed by R4 and R3. Furthermore, high throughput analysis showed that the Thauera performing partial denitrification, Ignavibacterium performing dissimilatory nitrate reduction to ammonium or nitrite were also present in all reactors, more abundant in R4, confirming that the higher nitrogen removal efficiency in R4 was attributed to the synergistic relationship of other nitrogenous genera with anammox. The higher abundance of PD and DNRA in the reactor with the coupled treatment of nano-zero valent iron and magnetic field, achieved in this research, opens the opportunity of complete nitrogen removal via synergistic partial-denitrification, anammox, and DNRA (SPDAD) process.